2019
DOI: 10.1186/s12958-019-0482-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-fat diets on fetal growth in rodents: a systematic review

Abstract: Background Maternal nutrition during pregnancy has life-long consequences for offspring. However, the effects of maternal overnutrition and/ or obesity on fetal growth remain poorly understood, e.g., it is not clear why birthweight is increased in some obese pregnancies but not in others. Maternal obesity is frequently studied using rodents on high-fat diets, but effects on fetal growth are inconsistent. The purpose of this review is to identify factors that contribute to reduced or increased feta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 149 publications
2
27
0
2
Order By: Relevance
“…One outstanding question is whether the detrimental effects on offspring skeleton are driven by maternal obesity, maternal HFD, or both. In humans, most studies explore the effects of obesity during pregnancy, commonly assessed by measuring body mass index rather than dietary patterns (46). In rodents, the majority of studies implemented a maternal HFD regime at least 4 weeks before mating.…”
Section: Current Research Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…One outstanding question is whether the detrimental effects on offspring skeleton are driven by maternal obesity, maternal HFD, or both. In humans, most studies explore the effects of obesity during pregnancy, commonly assessed by measuring body mass index rather than dietary patterns (46). In rodents, the majority of studies implemented a maternal HFD regime at least 4 weeks before mating.…”
Section: Current Research Gapsmentioning
confidence: 99%
“…Unlike in humans, changing the diet of a rodent from HFD to CD induces rapid weight loss (47). This could be overcome using embryo transfer following pre-conception maternal HFD, placing embryos into CD-fed recipients (46).…”
Section: Current Research Gapsmentioning
confidence: 99%
“…There is strong evidence that high caloric intake has negative impacts on principal body functions, such as endocrine effects, altered liver metabolism, and cholesterol imbalance [137][138][139]. Developmental programming, an action associated with nutrition during pregnancy and early life, imposes continual effects on the health of offspring, as shown through the reproductive repercussions of high-fat diets (HFD) [140,141]. It has been demonstrated that high fat and sugar intake induces alterations in circadian clock function, which seems to be a factor in female reproductive timing, since such changes may harm synchronization between circadian rhythmicity and central or peripheral components.…”
Section: High Fat Diet and Time-restricted Feeding Regulationmentioning
confidence: 99%
“…It has been demonstrated that high fat and sugar intake induces alterations in circadian clock function, which seems to be a factor in female reproductive timing, since such changes may harm synchronization between circadian rhythmicity and central or peripheral components. Recently, several studies have shown that high caloric intake leads to premature aging, altered sleep, and disruption in circadian rhythmicity [141][142][143][144]. Highlighting their significance, high-fat diet intake affects the ovarian circadian clock [145].…”
Section: High Fat Diet and Time-restricted Feeding Regulationmentioning
confidence: 99%
“…17 However, such studies are inevitably subject to a range of confounding factors that limit their ability to identify causality. Because they can eliminate confounds, animal models have advanced our understanding of the biological mechanisms involved in maternal overnutrition, 20,21 including high-sugar diets. 22 Given SSB intake is a prime target for the prevention of excessive weight gain during pregnancy, it is important to validate the epidemiological findings [17][18][19] in animal models.…”
Section: Introductionmentioning
confidence: 99%